RELATIONSHIP BETWEEN MACERATION AND WOUND HEALING ON DIABETIC FOOT ULCERS IN INDONESIA: A PROSPECTIVE STUDY - Haryanto, Haryanto; Arisandi, Defa; Suriadi, Suriadi; Ogai, Kazuhiro; Sanada, Hiromi; Okuwa, Mayumi; Sugama, Junko (ETN Centre Indonesia, 2016)
Background: Maceration results in enhancement of the wound area and infection. This condition is caused by a breakdown of the skin resulting in an open wound so that the wound area is enhanced and contaminated by microorganisms. Consequently, wound healing is delayed and quality of life is negatively affected. The prevention of maceration is important, and exudate management offers a way to prevent maceration. Exudate management can reduce the healing time, exudate, and frequency of dressing changes, and improve patient quality of life. Aims: The aim of this study was to clarify the relationship between maceration and wound healing. Methods: A prospective longitudinal design was used in this study. The wound condition determined the type of dressings used and the dressing change frequency. A total of 62 participants with diabetic foot ulcers (70 wounds) were divided two groups: non-macerated (n = 52) and macerated wounds (n = 18). Each group was evaluated weekly using the Bates?Jensen Wound Assessment Tool with follow-ups until week 4. Results: The Mann?Whitney U test showed that the changes in the wound area in week 1 were faster in the non-macerated group than the macerated group (P = 0.02). The Pearson correlation analysis showed a moderate correlation between maceration and wound healing from enrolment until week 4 (P = 0.002). After week 4, the Kaplan?Meier analysis showed that the non-macerated wounds healed significantly faster than the macerated wounds (log-rank test = 19.378, P = 0.000). The Cox regression analysis confirmed that maceration was significant and independent predictor of wound healing in this study (adjusted hazard ratio, 0.324; 95% CI, 0.131?0.799; P = 0.014). Conclusion: The results of this study demonstrated that there is a relationship between maceration and wound healing. Changes in the wound area can help predict the healing of wounds with maceration in clinical settings. Keywords: Wound maceration; wound healing, diabetic foot ulcers.